Modeling Robotic Arm with Six-Degree-of-Freedom Through Forward Kinematics Calculation Based on Deep Learning - Q. Nguyen, Thanh; B. Pham, Khien; Thi Kim Chi, Duong (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Modeling a robotic arm is one of the popular types of CNC (computer numerical controller) machines that are suitable for specialized training and meeting the high demand in today's manufacturing industry. However, research and development of robotic arm models in Vietnam are still limited and primarily concentrated in large foreign-invested factories. This research develops a forward kinematics problem model for a six-degree-of-freedom robotic arm, which is a common type of model in the industry today, using artificial intelligence (AI). This study details each step, from axis transformations, translations, and rotations to determine the position of each link at various times, based on deep learning. It establishes the relationship between each step of the robot designed from the virtual model by AI. Furthermore, the study will use calculations and simulations to compare and contrast the deviations and verify the results. In the future, the study will incorporate inverse kinematics and dynamics problems to create a comprehensive study of the six-degree-of-freedom robotic arm model.